2002
DOI: 10.1523/jneurosci.22-23-10399.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Regulating Activity-Dependent Release of Native Brain-Derived Neurotrophic Factor from Hippocampal Neurons

Abstract: Brain-derived neurotrophic factor (BDNF) plays a critical role in activity-dependent modifications of neuronal connectivity and synaptic strength, including establishment of hippocampal long-term potentiation (LTP). To shed light on mechanisms underlying BDNF-dependent synaptic plasticity, the present study was undertaken to characterize release of native BDNF from newborn rat hippocampal neurons in response to physiologically relevant patterns of electrical field stimulation in culture, including tonic stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
284
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(314 citation statements)
references
References 82 publications
27
284
2
1
Order By: Relevance
“…This secretion could be blocked by AMPA and NMDA antagonists and was shown to require an extracellular calcium influx (Hartmann et al, 2001). In other work, it was suggested that BDNF release was prevented by manipulations that interfered with release of calcium from intracellular stores (Balkowiec and Katz, 2002). How some studies differ from ours, however, is that they find that steady-state depolarization cannot elicit BDNF secretion (Kohara et al, 2001;Kojima et al, 2001;Gartner and Staiger, 2002), a result suggested to occur because the intracellular calcium levels required for BDNF secretion can only be obtained through repeated action potential firing.…”
Section: Discussionmentioning
confidence: 97%
“…This secretion could be blocked by AMPA and NMDA antagonists and was shown to require an extracellular calcium influx (Hartmann et al, 2001). In other work, it was suggested that BDNF release was prevented by manipulations that interfered with release of calcium from intracellular stores (Balkowiec and Katz, 2002). How some studies differ from ours, however, is that they find that steady-state depolarization cannot elicit BDNF secretion (Kohara et al, 2001;Kojima et al, 2001;Gartner and Staiger, 2002), a result suggested to occur because the intracellular calcium levels required for BDNF secretion can only be obtained through repeated action potential firing.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have also suggested that BDNF itself could induce (Messaoudi et al, 1998) or facilitate (Kovalchuk et al, 2002) LTP expression in the hippocampus. Additional findings that high-frequency stimulation or more natural theta patterns of afferent activity upregulates BDNF expression further corroborate its role in synaptic plasticity (Gooney and Lynch, 2001;Balkowiec and Katz, 2002). Mechanisms underlying the function of BDNF in plasticity include presynaptic (Gottschalk et al, 1998;Pozzo-Miller et al, 1999;Jovanovic et al, 2000;Xu et al, 2000;Zakharenko et al, 2003;Tyler et al, 2006) or postsynaptic actions Lin et al, 1998;Di Luca et al, 2001;Kovalchuk et al, 2002) as well as coordinate pre-and postsynaptic processes (Alder et al, 2005;Gartner et al, 2006).…”
Section: Introductionmentioning
confidence: 86%
“…Patterned electrical activity and the ensuing changes in Ca 2ϩ transients, opposed to steady firing activity, preferentially stimulate the transcription and secretion of neurotrophins (Balkowiec and Katz 2002). Moreover, electrical activity tightly regulates the expression of neurotrophin receptors, giving insight into a mechanism by which neurotrophins may selectively affect electrically active neurons.…”
Section: Expression Of Ca V 31 Channels In the Inner Ear During Devementioning
confidence: 99%